2020
DOI: 10.26434/chemrxiv.12262010.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polymer-Assisted Modification of Metal-Organic Framework MIL-96 (Al): Influence on Particle Size, Crystal Morphology and Perfluorooctanoic Acid (PFOA) Removal

Abstract: <div><b>Abstract</b></div><div>A new synthesis method was developed to prepare an aluminum-based metal organic framework (MIL-96) with a larger particle size and different crystal habits. A low cost and water-soluble polymer, hydrolyzed polyacrylamide (HPAM), was added in varying quantities into the synthesis reaction to achieve >200% particle size enlargement with controlled crystal morphology. The modified adsorbent, MIL-96-RHPAM2, was systematically characterized by SEM, XRD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…It has been reported that the sorption capacity of chromium analog MOF was higher as compared to iron analog MOF due to stronger interaction between the metal node and sulfur moieties of PFOS molecule (Barpaga et al 2019). Another study developed an aluminum-based MOF for PFOA uptake from water at a laboratory scale and sorbent performance was compared with AC (Hakim Mohd Azmi et al 2020). The much stronger adsorption capacity of PFOA (340 mg/g) compared to AC (120 mg/g) was observed, and which was attributed to the electrostatic bonds formed between the anionic functional group of PFOA and the aluminum-based MOF.…”
Section: Metal Organic Framework (Mofs)mentioning
confidence: 99%
“…It has been reported that the sorption capacity of chromium analog MOF was higher as compared to iron analog MOF due to stronger interaction between the metal node and sulfur moieties of PFOS molecule (Barpaga et al 2019). Another study developed an aluminum-based MOF for PFOA uptake from water at a laboratory scale and sorbent performance was compared with AC (Hakim Mohd Azmi et al 2020). The much stronger adsorption capacity of PFOA (340 mg/g) compared to AC (120 mg/g) was observed, and which was attributed to the electrostatic bonds formed between the anionic functional group of PFOA and the aluminum-based MOF.…”
Section: Metal Organic Framework (Mofs)mentioning
confidence: 99%